2017
DOI: 10.3389/fcimb.2017.00091
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Integrated Hepatitis B Virus DNA Using CRISPR-Cas9

Abstract: The presence of hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) and the permanent integration of HBV DNA into the host genome confers the risk of viral reactivation and hepatocellular carcinoma. Nucleoside/nucleotide analogs alone have little or no capacity to eliminate replicative HBV templates consisting of cccDNA or integrated HBV DNA. Recently, CRISPR/Cas9 technology has been widely applied as a promising genome-editing tool, and HBV-specific CRISPR-Cas9 systems were shown to effectively me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 55 publications
1
81
0
1
Order By: Relevance
“…Intriguingly, they also have shown that the combination of the sgRNAs was more efficient in suppressing HBV protein in comparison to individual sgRNAs . In agreement with previous study, several other groups have shown significant drop in the total level of HBV DNA and HBV proteins via anti HBV sgRNAs against different regions of HBV genome . As indicated before, elimination of HBV cccDNA in the hepatocyte nuclei seems to be impossible with current therapies; therefore, the removal of cccDNA is an important aim in eradicating of HBV infection.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Intriguingly, they also have shown that the combination of the sgRNAs was more efficient in suppressing HBV protein in comparison to individual sgRNAs . In agreement with previous study, several other groups have shown significant drop in the total level of HBV DNA and HBV proteins via anti HBV sgRNAs against different regions of HBV genome . As indicated before, elimination of HBV cccDNA in the hepatocyte nuclei seems to be impossible with current therapies; therefore, the removal of cccDNA is an important aim in eradicating of HBV infection.…”
Section: Introductionsupporting
confidence: 84%
“…However, several studies have demonstrated that HBV cccDNA could be cleaved by CRISPR/Cas9 system. They have shown that targeting different ORFs using a single sgRNA might be effective elimination cccDNA but give better results if multiple sgRNAs target different loci …”
Section: Introductionmentioning
confidence: 99%
“…19,20 A number of experimental systems provide a clear proof that this approach has the potential to disrupt the HBV genome and inhibit viral replication, thereby contributing to the development of novel therapeutic strategies aiming to cure HBV infection. [21][22][23] Thus, it is necessary to design specific guide RNAs (gRNAs) for HBV preS1/preS2/S ORF to elucidate the precise role of HBsAg and its underlying mechanism in hepatocarcinogenesis. Furthermore, targeting HBsAg using the CRISPR /Cas9 system may open up new avenues for anti-cancer therapeutic strategies for HBV-HCC. In the present study, we designed specific single guide RNAs (sgRNAs), and for the first time established HBsAg knockout HCC cell lines by using CRISPR/Cas9 system-mediated genetic engineering.…”
mentioning
confidence: 99%
“…Later on, Karimova et al also used Cas9 nickase to target the conserved sequences present in X and S HBV genome, which destroyed the cccDNA of HBV together with chromosomally integrated HBV genome inhibiting the viral replication. Strikingly, experiments of Li et al recently proved that by using CRISPR/Cas9 it is possible to completely excise 3175bp‐integrated HBV DNA along with the distortion of cccDNA of HBV.…”
Section: Implication Of Crispr/cas9 In Combating Oncovirusesmentioning
confidence: 99%